A Fast 3-D finite element modeling algorithm for land transient electromagnetic method with OneAPI acceleration - Yang, Xiaodong; Wu, Xiaoping; Yue, Mingxin (Computers & geosciences, 2022)
The land transient electromagnetic (TEM) method is a geophysical prospecting method with a wide range of applications. In this paper, we develop an algorithm that carries out 3-D TEM modeling for loop-source devices. The algorithm is based on the time-domain finite element method with unstructured edge-based meshes, and an unconditional stable adaptive time-stepping method is developed to acquire stable solutions. We verify the algorithm with a 1-D analytical solution. And as case studies, we discuss the TEM responses of both large-loop and small-loop devices in the presence of topography. It is found that the modeling accuracy is more sensitive to space meshing than time discretization. The proposed algorithm is packed as software, TEMF3DT, which is open-source and publicly available together with the above-mentioned sample models. TEMF3DT is designed for PC users, but is also constructed through a higher-level MPI parallelization and a lower-level OpenMP parallelization for potential workstation or cluster uses. Also, TEMF3DT is accelerated by the modern Fortran and Intel OneAPI library to deliver state-of-the-art computational efficiency. •Stable 3-D TEM modeling algorithm for a wide range of conductivity.•Compatible with complex topographic models.•Open-source software for various types of TEM devices and transmitting waveforms.